The 10th Annual scientific Meeting of the Irish Association of physicists in medicine (IAPM ASM 2019). (July 2020) - Kenny, Emer; Lavin, David; Colgan, Niall; McClean, Brendan; Cournane, Sean
Abstract: The Irish Association of Physicists in Medicine (IAPM) is an association of medical physicists in Ireland. The IAPM was founded in 2010 with the merger of the Association of Physical Scientists in Medicine (APSM) and the Irish Radiotherapy Physics Group (IRPG). The 10th Annual Scientific Meeting of the IAPM was held in Dublin on 23rd March 2019. This editorial summarises the proceedings of the day including invited speakers, diagnostic imaging and radiotherapy sessions, the Young Investigator Grant, the Early Careers bursary, joint session and poster presentations. A special issue of Physica Medica was dedicated to the event featuring a number of research papers.